Analisis Pemanfaatan Gadai Sawah Ditinjau Dari Segi Hukum Islam (Diteliti Di Desa Cijaku Kabupaten Lebak Banten) - Lu’luul Karimah, Adhiyani (STAI Publisistik Thawalib Jakarta, 2022)
In Article 1150 of the Civil Code, a pawn is a right obtained by a person who owes a debt to a movable property, which is handed over to him by a debtor or by another person on his behalf, and which gives the debtor the power to take full repayment of the goods in full. take precedence over other debtors; with the exception of the cost of auctioning the item and the costs that have been incurred to save it after the item has been mortgaged, which costs should take precedence. In the form of field pawning carried out in Cijaku Village, in general the pawning party borrows money or gold to the pawn recipient with a guarantee of paddy fields, for a period of time that is determined or not determined at all, during which the paddy fields are managed by the recipient of the pawn. Pawn fields are the results used by both parties. With a percentage that is generally 50%-50%. The nominal amount of the loan given by the pawnee to the pawnbroker is not adjusted to the area and condition of the land, but according to the agreement of both parties.